A saúde do servidor público em sua dimensão social: política de saúde do servidor, relações sociais, protagonismo e determinantes sociais - Silva, Maria da Conceição Clarindo Cavalcante da (2012)
This thesis aims to investigate and analyze the health of the Public Servant and the Integral Health Care Politics to Federal Public Servants (IHCPFPS) concerning these Servants developed by the Reference Unit of Integral Health Care Subsystem of Servants, deployed at the Federal University of Alagoas (Ufal), responsible for health actions directed to the Public Servants and recommended byIHCPFPS. To investigate and analyze the situations of health and work social conditions to which public servants are exposed in the Brazilian state apparatus, placed in the University Hospital Professor Alberto Antunes (Hupaa) of that university. Because it is a social category fragmented and stratified hierarchy of dominant and dominated the working class, was selected one of the positions with which the research would be developed. It was used as a parameter for the selection of social subjects, those who needed most to be absent at work due to health issues, therefore they have health issues and diseases. Assistants and Nurses fromUniversity Hospital - hupaa-Ufal- were interviewed. The socioeconomic and cultural profiles of these workerswere designed as well as it was found what are the possibilities of their role as a social determinant in the effectiveness of the IHCPFPS, so as to promote changes in social relations of work, overcoming the precarious conditions and present subalternity. Suggestions are presented to effect a policy which focus on labor relations and the participation of these workers. Without a leading role, it is concluded that the State, through the IHCPFPS, will fulfill its role on control the health of the public servants, but their health shall not become effective in its entirety, bringing up the work processes and social determinants, as it means, the social health of the public servant